The dynamic dialectic relationship of empirical data and theoretical concepts. A framework for documenting and understanding social phenomena - Chtouris, Sotiris (The Greek Review of Social Research, 2019)
The present paper presents a specific research methodology instructed by the interest to study social reality as a coherent appearance of social phenomena, as well as social entities involved in them. In this context, different data forms are identified, along with collection and processing methods, in conjunction with definition of concepts about real social phenomena. In this effort, theoretical models are used, inspired by different sociological and philosophical schools, that emerge having some selective affinities in their research method of the real world. In this context, we proceed to a combined approach, namely elements of empirical positivism with elements of dialectical realism, with the main aim to understand theoretical work as a constituent part of empirical research and vice versa, that is empirical data as constituent part of modern sociological theory.